TRPM6 acts as a prognostic biomarker and mediates Mg2+ dependent tumor suppression in colon adenocarcinoma - Cao, Lichao; Ren, Yuxin; Yu, Xinru; Wang, Sihan; Zhang, Hezi; Chen, Erfei (Frontiers in Immunology, 2026)
IntroductionColon adenocarcinoma (COAD) is a malignant neoplasm derived from colonic epithelial cells with poor prognosis in advanced stages. This study aimed to identify critical molecular regulators of COAD and develop robust biomarkers for prognosis and therapy.MethodsTranscriptome data from public databases were analyzed: differential expression of TRPM family genes in COAD and pan-cancer pathogenic associations of TRPM6 were assessed via the Wilcoxon test, with analyses of consensus molecular subtypes, clinical relevance, and survival also performed. TRPM6-regulated differentially expressed genes (DEGs) were identified for functional enrichment, and immune/tumor microenvironment correlations were evaluated using the Spearman test. In vitro, HCT116 and SW480 cells were transfected with TRPM6 siRNAs, with proliferation (CCK-8), migration (Transwell), and marker expression (RT-qPCR) assessed.Results and DiscussionThe study showed TRPM family genes, particularly TRPM4 and TRPM6, had differential expression across COAD subtypes/stages, with high expression correlating with favorable prognosis. TRPM6 regulates cancers via neural pathways, associates with immune/tumor microenvironments, and has pan-cancer diagnostic value. TRPM6 knockdown promoted colon cancer cell proliferation and migration, while concurrent TRPM6 knockdown and high Mg2+ treatment attenuated Mg2+-mediated tumor suppression. These findings highlight TRPM6 as a pivotal mediator of Mg2+ functions and a valuable candidate for COAD prognostic classification and therapeutic intervention, providing a foundation for future studies on its regulatory roles in tumor progression and Mg2+-based therapies.